Sleeping habits of adolescents in relation to their physical activity and exercise output: results from the ELSPAC study - Máchal, Jan; Zlámal, Filip; Kukla, Lubomír; Švancara, Jan; Pikhart, Hynek; Bienertová-Vašků, Julie (Journal of epidemiology and community health, 2018)
BACKGROUND: Little is known about the effects of physical activity and fitness on sleep timing parameters in adolescence. METHODS: We investigated the development of sleep timing between age 8 and 15 and its association with physical fitness at age 15 in 787 adolescents (408 males, 379 females). Physical fitness was measured using the physical work capacity (PWC) protocol. Information on sport activity was collected at ages 11 and 15. Finally, the contribution of other covariates (sex, body mass index (BMI), parental education and occupational skill level) to the association between sleep parameters and physical fitness was evaluated. The correlation of BMI and physical fitness was assessed separately. RESULTS: Mild correlation of sleep duration at ages 8 and 15 was observed (r=0.08-0.16). Higher sport activity participation and physical fitness were found to be mildly associated with delayed bedtime and reduced sleep duration; the association with bedtime was significant after adjustment for all covariates. Sport activity at age 11 was not associated with sleep timing at age 15. Interestingly, higher BMI was linked to delayed bedtime and higher physical fitness. CONCLUSION: Our findings do not support existing hypotheses suggesting the association of low physical activity and fitness with shorter sleep duration and high BMI in a generally non-obese adolescent population without severe sleep restriction.
Keywords: sleep; Female; dítě; exercise test; ženské pohlaví; Adolescent Behavior; longitudinální studie; Adolescent; adolescents; lidé; cvičení; Habits; physical activity; prospektivní studie; spánek; Male; Prospective Studies; Czech Republic; mladiství; index tělesné hmotnosti; Sleep; Česká republika; Child; zvyky; mužské pohlaví; Body Mass Index; Exercise; chování mladistvých; Longitudinal Studies; Humans